Utility-value change and the role of emotional cost in video-based learning: a matter of student teachers’ interpretation of experience - Dehne, Mathias; Gröschner, Alexander (Frontiers in Psychology, 2023)
Video is a popular learning tool enhancing student teachers' reflection upon their teaching without situational pressure to act as in the classroom. Videos of one's teaching provide information unavailable in texts (e.g., information about students' mood), and so has research emphasized their promises compared to typically implemented text-based methods (e.g., lesson protocols). However, neither does simple video watching give a guarantee for learning, nor does it automatically activate emotional and motivational processes. To date, no social-psychological intervention has systematically targeted student teachers' utility values about reflections and investigated the role of emotional costs, such as fear of failure or perceived psychological threat. These so-called utility-value interventions aim for humans to systematically re-reflect a topic's or task's value for future, possibly career-related goals. In this study, student teachers reflecting on their teaching using video (intervention group) or a protocol (control group) were required to think about their learning experiences with the respective method systematically (intervention group) or unsystematically (control group).Three months after the intervention, utility values had increased moderately compared to student teachers in the control group. Emotional cost predicted changes positively in the intervention group showing that student teachers using video need systematic opportunities to integrate their experiences.